Os Simpsons no ensino de geografia: uma análise de mediação didática no 9º ano do ensino fundamental - Sousa, Jailson Silva De (2024)
The teaching of Geography, from the perspective of Milton Santos, should be centered on space, a set of systems and actions in which man is the transforming agent. Therefore, he should be and be aware of his actions and capabilities. Given this importance, Milton Santos argued that Geography teaching should focus on geographical space, and classes should teach students to read the world. Only then would we be training, as Paulo Freire defends, true citizens. However, we constantly witness questions such as "what is Geography for?" or "I won't use Geography for anything!". These statements make it clear that the mediation between Geography teaching and the student is not taking place. The complexities of geographical space are not being learned, and the objective of Geography teaching is not present in thousands of classrooms across Brazil. This perception encouraged me to seek methodological paths that would enable an effective teaching-learning relationship centered on a conscious elaboration of the concepts studied. This research is committed to the use of an animated series as a resource for mediation between what is intended to be taught and how to engage students, inserting them in the process of understanding the content. This dissertation, developed within the scope of the Graduate Program in Teaching in Basic Education (Professional Master's) of the Center for Teaching and Research Applied to Education at the Federal University of Goiás (PPGEEB-CepaeUFG), had as its fundamental objective to investigate the potential of the animated series The Simpsons in mediating the teaching of skills and competencies related to geographical concepts in 9th-grade elementary school classes. The provoking problem of this research revolves around verifying the potential of using an animated series in Geography classes in the quest to develop an engaging teaching-learning relationship in the classroom, involving students in geographical themes. The research is based on the perspective of Geography teaching and on research by Cavalcanti (2012, 2013), Castrogiovanni (2010), Straforini (2008), Carlos (1999), Pontuschka, Paganelli and Cacete (2009), Castrogiovanni, Callai and Kaercher (2017) and Castellar (2022) on the relationship between teaching and media; Barbosa (1999; 2009), Moran (2000), Leão and Leão (2008), Santos (2022), Kenski (2005) and Barbosa (1999) to understand the importance of mediation in the teaching-learning process; Silva (2010; 2007), Domingos (2012) and Kenski (2003), among others. This research followed a qualitative action research methodological perspective, developed in a State Military Police School in the state of Goiás in the city of Aparecida de Goiânia, in a 9th-grade class. Data were collected through the researcher's experience in the field school, student involvement with the proposed activities, reports, and activities. The result of this research consists of this dissertation and an educational product entitled The Simpsons in geography teaching: didactic mediation for the 9th grade of elementary school. This product aims to contribute to the teaching practice of Geography teachers in basic education, offering a collection of didactic sequences with suggestions for episodes of The Simpsons series, in addition to proposals for classes and activities focused on the contents aimed at the 9th grade of Elementary School.